The crystal structure of the catalytic domain of tau tubulin kinase 2 in complex with a small‐molecule inhibitor. Issue 3 (5th March 2020) - Marcotte, Douglas J.; Spilker, Kerri A.; Wen, Dingyi; Hesson, Thomas; Patterson, Thomas A.; Kumar, P. Rajesh; Chodaparambil, Jayanth V.
Abstract : The first crystal structure of the kinase domain of tau tubulin kinase 2 in complex with a small‐molecule inhibitor is described. Abstract : Tau proteins play an important role in the proper assembly and function of neurons. Hyperphosphorylation of tau by kinases such as tau tubulin kinase (TTBK) has been hypothesized to cause the aggregation of tau and the formation of neurofibrillary tangles (NFTs) that lead to the destabilization of microtubules, thereby contributing to neurodegenerative diseases such as Alzheimer's disease (AD). There are two TTBK isoforms with highly homologous catalytic sites but with distinct tissue distributions, tau phosphorylation patterns and loss‐of‐function effects. Inhibition of TTBK1 reduces the levels of NFT formation involved in neurodegenerative diseases such as AD, whereas inhibition of TTBK2 may lead to the movement disorder spinocerebellar ataxia type 11 (SCA11). Hence, it is critical to obtain isoform‐selective inhibitors. Structure‐based drug design (SBDD) has been used to design highly potent and exquisitely selective inhibitors. While structures of TTBK1 have been reported in the literature, TTBK2 has evaded structural characterization. Here, the first crystal structure of the TTBK2 kinase domain is described. Furthermore, the crystal structure of human TTBK2 in complex with a small‐molecule inhibitor has successfully been determined to elucidate the structural differences in protein conformations between the two TTBK isoforms that could aid in SBDD for the design of inhibitors that selectively target TTBK1 over TTBK2.